Escribimos textos funcionales: cartas, tarjetas y avisos - Muñoz Marin, Doris Elizabeth (2018)
The present reseach to the professional sufficiency is based to promote the significant learning achievement related to the texts elaboration such as letters, cards and notices in the students from first gradef High School, knowing these kind texts are used by our students very often. The learning session belongs to communication Area and was developed taking into account the recommendations to the communication approach proposed by the Ministry of Education Area, as well as the didactic processes necessary to achieve significant learning in the ability: Write various texts in mother tongue. The learning session will be evaluated by an observation sheet aid, to verify the achievement abilities and evidence necessary for the elaboration their functional texts: letters, cards and notices.